ANALISIS PERAN MASYARAKAT ADAT DALAM MELESTARIKAN TRADISI BUCANGEH SEBAGAI WUJUD PERTAHANAN SOSIAL BUDAYA DI DESA HAMPARAN PUGU SEMURUP KABUPATEN KERINCI - Putri Nabela; Priazki Hajri; Hendra (STKIP Subang, 2026)
This research is motivated by the decline of the Bucangeh Tradition in Hamparan Pugu Semurup Village, Kerinci Regency, due to the influence of modernization, changes in community mindsets, and the high cost of performing the tradition. The Bucangeh Tradition is a cultural heritage of indigenous communities, meaning it purifies babies, expresses gratitude, and introduces babies to their social and natural environment. This study aims to determine the role of indigenous communities in preserving the Bucangeh Tradition and the challenges faced in maintaining this tradition. This study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The informants consisted of traditional leaders, uhang nge nyangeh, and indigenous community members selected using purposive sampling. Data were analyzed through data reduction, data presentation, and drawing conclusions. Data validity was tested using triangulation of sources, techniques, and time. The results indicate that indigenous communities play a crucial role in preserving the Bucangeh Tradition through the implementation of the tradition, the transmission of cultural values ​​to the younger generation, and providing education on the importance of maintaining the tradition. The community also employs various preservation strategies to ensure the tradition remains recognized and practiced. However, preserving the Bucangeh Tradition faces challenges such as declining interest from the younger generation, the influence of modernization, and the high cost of performing the tradition. The conclusion of this study indicates that indigenous communities are still striving to maintain the Bucangeh Tradition as a cultural identity of the Hamparan Pugu Village community, ensuring its sustainability and passing it on to future generations.